Generation, structure and properties of the modified welding seams - F. G. Lovshenko; A. I. Khabibulin (Литьë и металлургия)
Preparation, structure and properties of modified welds by using electrodes with coatings, which contain, along with classical components, a modifying ligature. The ligature is mechanically and thermally synthesized composite submicrocrystalline powders with nanosized inclusions of aluminum oxides. Reactionary mechanical alloying is an effective technology of obtaining nanocrystalline modifying ligatures and modifiers. The use of electrodes with an experimental coating containing a mechanically alloyed, composite ligature to resolve transcrystalline type of structure of the weld metal and reduce the grain size by 2,5–3,0 times (from № 8–9 to № 11–12) reduces by 20–30% the threshold of cold brittleness and increase by 15–25% of mechanical properties of the weld metal.